2020
DOI: 10.1080/08856257.2020.1792714
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a dual system: motivation for teachers to study special education

Abstract: Special educators are considered essential in schools, both in the regular system and in the separate special needs system. It is important to understand how special education is envisioned among teachers who choose further study in this field. The aim of this study is to gain more knowledge about what motivates teachers to gain further qualifications to become special educators. The study is based on 158 written self-reports from students studying special education. These reports were analysed using thematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…First, by noticing moments when they experience joy, success, or even humor, teachers gain important insight regarding their expectations of what it means to be an effective educator and can reorient themselves to their core priorities and goals. Although many special educators enter the field with a passion for teaching students who have been marginalized by the education system (Lavian, 2013;Lindqvist et al, 2020), this passion is often challenged by unmanageable workloads (Bettini et al, 2017), competing messages about their roles (Shepherd et al, 2016), and isolation and misunderstanding from general education colleagues and administrators (Bettini et al, 2021). Noting the moments in which they experience positive emotions can help special educators to revive their original passion for the work.…”
Section: Using Emotional Data To Advocate For Professional Supportsmentioning
confidence: 99%
“…First, by noticing moments when they experience joy, success, or even humor, teachers gain important insight regarding their expectations of what it means to be an effective educator and can reorient themselves to their core priorities and goals. Although many special educators enter the field with a passion for teaching students who have been marginalized by the education system (Lavian, 2013;Lindqvist et al, 2020), this passion is often challenged by unmanageable workloads (Bettini et al, 2017), competing messages about their roles (Shepherd et al, 2016), and isolation and misunderstanding from general education colleagues and administrators (Bettini et al, 2021). Noting the moments in which they experience positive emotions can help special educators to revive their original passion for the work.…”
Section: Using Emotional Data To Advocate For Professional Supportsmentioning
confidence: 99%
“…Liksom Skrtic (1991) fokuserar Abbott (1988) på professionella aktörer och arbetsfördelning i samhälleliga system. Inom såväl pedagogisk som specialpedagogisk forskning har det visat sig fruktbart att undersöka hinder och möjligheter till lärande och deltagande utifrån hur olika yrkesgrupper förhandlar sin jurisdiktion på arbetsplatsen (se Göransson et al, 2015b;Sandström et al, 2019;Klang et al, 2017;Lindqvist et al, 2020). Som analysverktyg har därför Abbotts (1988) teori om professioners arbetsfördelning och jurisdiktion använts för att förstå vilka hinder och möjligheter som kan uppstå för studenter i studiesvårigheter.…”
Section: Abbotts Teori Om Jurisdiktion Och Arbetsfördelningunclassified
“…Pre-service special educators have begun their development in a new profession, which includes an advisory and supervisory function in relation to general education teachers. Studies (Lindqvist et al, 2020) have reported the presence of a pattern within in-service special educators' perceptions about their work: They develop from general education teachers to specialeducation teachers through a greater focus on the supervision of other teachers. In-service special educators strongly emphasize that a central task in their job is to work with supervision and consultation in relation to general education teachers.…”
Section: Pre-service Special Educators' Relational Competence In Encounters With Students With Behavioral Difficultiesmentioning
confidence: 99%